2019
DOI: 10.1002/bit.27216
|View full text |Cite
|
Sign up to set email alerts
|

Rice lectin receptor‐like kinase provides salinity tolerance by ion homeostasis

Abstract: Sensing stress and activating the downstream signaling pathways is the imperative step for stress response. Lectin receptor‐like kinase (LecRLK) is an important family that plays a key role in sensing stress conditions through lectin receptor and activates downstream signaling by kinase domain. We identified the role of OsLecRLK gene for salinity stress tolerance and hypothesized its role in Na+ extrusion from cell. OsLecRLK overexpression and downregulation (through artificial miRNA) transgenic lines were dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 73 publications
(99 reference statements)
1
12
0
Order By: Relevance
“…The measurements of intracellular ion concentration in transgenic plants revealed that the OsRuvBL1a encoding gene is involved in lowering of the accumulation of sodium ions inside cells as compared with the corresponding wild types grown in identical conditions. Lower sodium ion accumulation in the salinity tolerant plants as compared to susceptible plants has also been reported earlier studies also (Kavitha et al 2012;Nath et al 2016;Passricha et al 2020;Zhang et al 2011). As a stress tolerance mechanism the plants are known to sequester excess Na + ions inside the intracellular compartments to protect the essential organelles and molecules from their deleterious effects (Blumwald 2000; Flowers and Colmer 2008).…”
Section: Isolation and Identi Cation Of Interacting Partners Of Osruvbl1a Through Yeast Two-hybrid Methodssupporting
confidence: 83%
See 1 more Smart Citation
“…The measurements of intracellular ion concentration in transgenic plants revealed that the OsRuvBL1a encoding gene is involved in lowering of the accumulation of sodium ions inside cells as compared with the corresponding wild types grown in identical conditions. Lower sodium ion accumulation in the salinity tolerant plants as compared to susceptible plants has also been reported earlier studies also (Kavitha et al 2012;Nath et al 2016;Passricha et al 2020;Zhang et al 2011). As a stress tolerance mechanism the plants are known to sequester excess Na + ions inside the intracellular compartments to protect the essential organelles and molecules from their deleterious effects (Blumwald 2000; Flowers and Colmer 2008).…”
Section: Isolation and Identi Cation Of Interacting Partners Of Osruvbl1a Through Yeast Two-hybrid Methodssupporting
confidence: 83%
“…Global climate change and population explosion make it compulsory to utilize the full genetic potential of plants for feeding the world population (Edgerton 2009;Godfray et al 2010;Passricha et al 2014;Passricha et al 2020). Abiotic stresses adversely affect the plants growth at various levels (Gao and Lan 2016;Passricha et al 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…During plant salt stress responses, multiple signaling cascade components are activated. RLKs have previously been shown to be involved in salt responses ( de Lorenzo et al, 2009 ; Ouyang et al, 2010 ; Lin et al, 2020 ; Passricha et al, 2020 ; Yuchun et al, 2021 ); however, the function of a unique group of RLKs, known as WAKs, in salt tolerance remains unclear. WAKs likely associate with pectin in the cell wall and are necessary for both cell expansion during development and mediation of the response to stresses ( Kanneganti and Gupta, 2011 ; Wang et al, 2012 ; Delteil et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…A Pisum sativum LecRLK, PsLecRLK, promotes tissue compartmentalization of sodium and ROS scavenging activity providing the alleviation of the ionic and osmotic environment during salinity stress (Vaid et al, 2015;Passricha et al, 2019). In addition, a rice LecRLK, Salt Intolerance 2 (SIT2) was identified for its role in salinity stress tolerance potentially through its function in Na + extrusion by manipulating SOS pathway (Passricha et al, 2020). Furthermore, Salt Intolerance 1 (SIT1), another rice L-type LecRLK, could be activated by NaCl and mediate salt sensitivity via the activation of MPK3/MPK6 leading to higher ethylene production and downstream ROS accumulation (Li et al, 2014;Zhao et al, 2019).…”
Section: Lecrlks In Plant Abiotic Stressmentioning
confidence: 99%
“…Furthermore, Salt Intolerance 1 (SIT1), another rice L-type LecRLK, could be activated by NaCl and mediate salt sensitivity via the activation of MPK3/MPK6 leading to higher ethylene production and downstream ROS accumulation (Li et al, 2014;Zhao et al, 2019). Although this L-type LecRLK has been predicted to bind monosaccharide or polypeptide, the rapid activation of SIT1 by external NaCl treatment, the requirement of SIT1 in the activation of MPK3/MPK6 by NaCl, and the requirement of its kinase activity for salt sensitivity imply that it plays an essential role in the signaling sensing and transduction of external Na + , either through directly getting activated by Na + or sensing the signal released by Na + (Li et al, 2014;Passricha et al, 2020) .…”
Section: Lecrlks In Plant Abiotic Stressmentioning
confidence: 99%